2020
DOI: 10.1128/msphere.00080-20
|View full text |Cite
|
Sign up to set email alerts
|

Early OXA-48-Producing Enterobacterales Isolates Recovered in a Spanish Hospital Reveal a Complex Introduction Dominated by Sequence Type 11 (ST11) and ST405 Klebsiella pneumoniae Clones

Abstract: Carbapenemase-producing Enterobacterales (CPE) have become an important public health concern. In our hospital, VIM enzymes were first detected in 2005, Klebsiella pneumoniae carbapenemase (KPC) enzymes in 2009, and OXA-48 enzymes in 2012. We assess the population biology of the first OXA-48-producing Enterobacterales isolates recovered in our hospital (2012 to 2013) where infections by other carbapenemases had been endemic for several years. Over a 21-month period, 71 isolates (61 Klebsiella pneumoniae, 5 Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Nevertheless, little is known at the genomic level about the initial colonization and subsequent dispersion of these isolates in hospitals. Most studies have analysed the specific bacterial clone and plasmid(s) responsible for the first cases detected [38]. Extending these analyses beyond the initial period and complete genome analysis of the corresponding isolates allows a better characterization of the colonizing strains and genes, revealing the relationships among isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, little is known at the genomic level about the initial colonization and subsequent dispersion of these isolates in hospitals. Most studies have analysed the specific bacterial clone and plasmid(s) responsible for the first cases detected [38]. Extending these analyses beyond the initial period and complete genome analysis of the corresponding isolates allows a better characterization of the colonizing strains and genes, revealing the relationships among isolates.…”
Section: Discussionmentioning
confidence: 99%
“…These plasmids share a highly conserved backbone and differ mainly by the presence/absence of various insertions; for simplicity, they are all referred to as pOXA-48 throughout the text. This plasmid type is frequently associated with K. pneumoniae high-risk clones 16 , such as the sequence types 11 (ST11), ST15, ST101, and ST405 6 , 15 , 17 , 18 , which are able to readily spread between hospitalized patients producing outbreaks of infections 19 , 20 . Previous epidemiological studies strongly suggested the possibility of within-patient pOXA-48 transfer 20 25 , indicating that pOXA-48 would be an ideal study system to investigate the nosocomial dissemination of carbapenem resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The bla oχA-48 gene is usually encoded in an IncL, broad-host-range conjugative plasmid called pOXA-48 8 (Figure S1). This plasmid is frequently associated with K. pneumoniae high-risk clones 12 , such as the sequence types 11 (ST11), ST15, ST101, and ST405 6,1315 , which are able to readily spread between hospitalized patients producing outbreaks of infections 16,17 . Previous epidemiological studies strongly suggested the possibility of within-patient pOXA-48 transfer 1721 , indicating that pOXA-48 would be an ideal study system to investigate the nosocomial dissemination of carbapenem resistance.…”
Section: Introductionmentioning
confidence: 99%